THE EFFECT OF FINANCIAL RATIOS ON PROFITABILITY OF INDONESIAN ISLAMIC BANKING BEFORE AND DURING THE COVID-19 PANDEMIC (2018-2021) - ulva ardiani; Damanhur Damanhur; Muammar Khadafi (J-MIND (Jurnal Manajemen Indonesia), 2023)
This study aims to analyze the effect of financial ratios on profitability (NOM), and look at differences in profitability (NOM) in Islamic Banking before and during the Covid-19 pandemic (2018-2021). The sampling technique used purposive sampling. The selected sample is 10 Islamic Commercial Banks in Indonesia for the period from 2018 to 2021. Financial ratios are measured by ROE, NPF, FDR, and BOPO and profitability is measured by NOM. The data analysis method used is multiple linear regression and non-parametric test (Wilcoxon test). The results showed that ROE and BOPO had a positive effect on NOM, while NPF and FDR had a negative effect on NOM, then there is no difference in net operating margin (NOM) before and during the covid-19 pandemic.